Unilateral multi-segmental leiomyomas: A report of rare case - Chandramohan Kudligi; Binod K Khaitan; Pradeep Vittal Bhagwat; Dinesh Prasad Asati (Wolters Kluwer Medknow Publications, 2013)
A 30-year-old female presented to us with multiple tender erythematous papules and nodules. These lesions showed multi-segmental distribution along 5 th cervical, 6 th dorsal, and 1 st sacral segments of right half of the body. Histopathological examination confirmed the clinical diagnosis of leiomyoma. Patient was started on nifedipine 10 mg thrice-daily with significant symptomatic improvement in 3 months. Though segmental distribution of leiomyoma is common, unilateral multi-segmental distribution has not been so far reported in the literature. Hence, the case is being reported for its rare presentation and the need for long-term follow-up in view of its association with aggressive renal carcinoma.